KONDISI BAKTERIOLOGIK PERALATAN MAKAN DI RUMAH MAKAN JOMBANG TIKALA MANADO - Henny J. Tumelap (Jurnal Kesehatan Lingkungan, 2011)
Tableware hygiene is poor have an important role in the growth of the spread of germs and poisoning. For that food equipment must be kept clean, in order to avoid contamination of pathogenic bacteria Escherichia coli is one of them as well as other contaminants. The purpose of this study was to determine the number of bacteria and Escherichia coli in the tableware used by Jombang Restorant Tikala Manado. The method used in this research is descriptive by laboratory analysis to determine the numbers and Escherichia coli bacteria on utensils used by Jombang Restorant Tikala Manado. The results showed that the results of laboratory examination of samples of tableware used by Jombang Restorant Tikala Manado, do not meet health requirements in accordance with RI Permenkes No.1098/Menkes/SK/VII/2003 on Hygiene Sanitation Requirements Restaurant. Of the 16 samples examined laboratory utensils all Not Eligible. Based on these results in the seller's expected to further improve food hygiene / sanitation, food hygiene, especially in the washing process of tableware and cutlery storage small so the likelihood of contamination in foods.